Polypropylene resin composition and molded article
Patent Information
- Application Number
- JP2021044733
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-18
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-18
AI Technical Summary
【0010】 本発明のポリプロピレン系樹脂組成物は、ボトルキャップ等の用途において、特にヒンジ部の耐白化性と耐衝撃性とを両立させることができる。
Smart Images

Figure 0007645108000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polypropylene resin composition having whitening resistance and impact resistance, and a molded article containing said composition. [Background technology]
[0002] In general, propylene resins are inexpensive and have excellent mechanical properties, hygienic compatibility, and moldability, and the appearance of molded products is also good, so they are used to manufacture molded products in a wide range of fields, such as food containers, beverage containers, and medical containers.
[0003] For container caps that require the contents to be filled with heat, such as caps for beverage containers and caps for liquid food containers, regardless of whether they are screw caps or hinge-type caps, polypropylene resins with excellent heat resistance are often used.
[0004] On the other hand, these container caps may be subjected to sudden stress loads when the product is removed from a mold in the manufacturing process. In addition, in the case of hinge-shaped caps, stress loads are applied to the hinge portion due to repeated bending. In the case of conventional polypropylene resin compositions, the sudden stress loads and the stress loads of repeated bending are likely to cause whitening, deformation, peeling, etc., which may impair the appearance of the cap itself and may reduce the function of the cap.
[0005] As a technique for preventing product defects typified by such whitening, Patent Document 1 discloses a polypropylene resin composition capable of providing a cap for a beverage bottle capable of suppressing the whitening caused by stress load during cap molding. Patent Document 2 discloses a polypropylene resin composition having excellent whitening resistance and impact resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-84393 A [Patent Document 2] Special Publication No. 2016-528356 Summary of the Invention [Problem to be solved by the invention]
[0007] Among caps, caps having a hinge portion that is repeatedly bent and curved are particularly susceptible to the whitening phenomenon occurring at the hinge portion. In addition, polypropylene resins are required to have high impact resistance, but attempting to achieve both whitening resistance and impact resistance tends to deteriorate the peel resistance of the hinge portion. On the other hand, increasing the tensile modulus in order to improve the hinge portion peel resistance and also improving whitening resistance tends to decrease the impact resistance.
[0008] An object of the present invention is to provide a polypropylene resin composition which is suitable for use in bottle caps and the like and which is capable of achieving both good whitening resistance and good impact resistance, particularly in the hinge portion. [Means for solving the problem]
[0009] The present inventors have found that the above object can be achieved by using a combination of two specific propylene-based copolymers and further blending a nucleating agent therein, and have thus completed the present invention. The present invention relates to, for example, the following [1] to [3]. [1] A polypropylene-based resin composition comprising 80 to 90 parts by mass of a propylene-based copolymer (A) satisfying the following requirements (A1) and (A2), 10 to 20 parts by mass of a propylene-based copolymer (B) satisfying the following requirements (B1) and (B2), and 0.01 to 0.6 parts by mass of a nucleating agent (D) (wherein the total of the propylene-based copolymer (A) and the propylene-based copolymer (B) is 100 parts by mass), and satisfying the following requirement (C1). (A1) The content of structural units derived from ethylene in the propylene-based copolymer (A) is 1.0 to 3.0% by mass. (A2) Intrinsic viscosity [η] of propylene copolymer (A) in decalin at 135°C (A) is 1.0~2.0dl / g. (B1) The content of structural units derived from ethylene in the propylene-based copolymer (B) is 20 to 40 mass %. (B2) Intrinsic viscosity [η] of propylene copolymer (B) in decalin at 135°C (B) is 1.0 to 2.0 dl / g, and the intrinsic viscosity ratio [η] of the propylene copolymer (B) / propylene copolymer (A) is (B) / [η] (A) is 0.8 to 1.4. (C1) The melt flow rate (MFR), measured in accordance with JIS K 7210 at 230°C under a load of 2.16 kg, is 10 to 50 g / 10 min. [2] The polypropylene resin composition according to [1], further satisfying the following requirements (C2) to (C4): (C2) The tensile modulus measured in accordance with JIS K 7161 is 800 to 900 MPa. (C3) The total energy of high-speed surface impact measured in a 0°C environment in accordance with the ASTM D 3763-02 high-speed impact test method is 20 J or more. (C4) A hard ball is dropped onto the center of a test piece obtained by injection molding, and the change in L value ΔL in L / a / b at the center of the test piece measured before and after the drop is 10 or less. [3] A molded article comprising the polypropylene resin composition according to [1] or [2]. Effect of the Invention
[0010] The polypropylene resin composition of the present invention can achieve both whitening resistance and impact resistance, particularly in the hinge portion, when used for bottle caps and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Polypropylene resin composition] The polypropylene resin composition of the present invention contains the propylene copolymer (A), the propylene copolymer (B) and the nucleating agent (D) described below, and satisfies the requirement (C1) described below.
[0012] The propylene-based copolymer (A) satisfies the following requirements (A1) and (A2). (A1) The content of structural units derived from ethylene in the propylene-based copolymer (A) is 1.0 to 3.0% by mass.
[0013] The propylene copolymer (A) is a copolymer obtained by copolymerizing propylene and ethylene, and has a content of structural units derived from ethylene of 1.0 to 3.0% by mass, preferably 1.0 to 2.8% by mass, and more preferably 1.0 to 2.6% by mass. If the content of structural units derived from ethylene in the propylene copolymer (A) is less than 1.0% by mass, peel resistance and whitening resistance may deteriorate, and if it is more than 3.0% by mass, deformation of the hinge portion may occur.
[0014] As long as the above conditions are satisfied, the propylene copolymer (A) may contain structural units derived from comonomers other than ethylene. (A2) Intrinsic viscosity [η] of propylene copolymer (A) in decalin at 135°C (A) is 1.0~2.0dl / g.
[0015] The propylene copolymer (A) has an intrinsic viscosity [η] in decalin at 135°C. (A) is 1.0 to 2.0 dl / g, preferably 1.1 to 1.8 dl / g, and more preferably 1.2 to 1.6 dl / g. (A) If the viscosity is less than 1.0 dl / g, deformation of the hinge portion may occur easily, whereas if the viscosity is more than 2.0 dl / g, peel resistance and whitening resistance may deteriorate.
[0016] The propylene-based copolymer (B) satisfies the following requirements (B1) and (B2). (B1) The content of structural units derived from ethylene in the propylene-based copolymer (B) is 20 to 40 mass %.
[0017] The propylene copolymer (B) is a copolymer obtained by copolymerizing propylene and ethylene, and has a content of structural units derived from ethylene of 20 to 40% by mass, preferably 20 to 35% by mass, and more preferably 20 to 30% by mass. If the content of structural units derived from ethylene in the propylene copolymer (B) is less than 20% by mass, the impact resistance may decrease and the hinge part may be easily deformed, whereas if it is more than 40% by mass, the peel resistance and whitening resistance may deteriorate.
[0018] As long as the above conditions are satisfied, the propylene-based copolymer (B) may contain structural units derived from comonomers other than ethylene. (B2) Intrinsic viscosity [η] of propylene copolymer (B) in decalin at 135°C (B) is 1.0 to 2.0 dl / g, and the intrinsic viscosity ratio [η] of the propylene copolymer (B) to the propylene copolymer (A) is (B) / [η] (A) is 0.8 to 1.4.
[0019] The propylene copolymer (B) has an intrinsic viscosity [η] in decalin at 135°C. (B) is 1.0 to 2.0 dl / g, preferably 1.2 to 1.9 dl / g, and more preferably 1.4 to 1.8 dl / g. (B) If it is less than 1.0 dl / g, the impact resistance may decrease, whereas if it is more than 2.0 dl / g, the peel resistance and whitening resistance may deteriorate.
[0020] Intrinsic viscosity ratio [η] of propylene copolymer (B) to propylene copolymer (A) (B) / [η] (A) is 0.8 to 1.4, preferably 0.9 to 1.4, and more preferably 1.0 to 1.4. (B) / [η] (A)If it is less than 0.8, peel resistance and whitening resistance may deteriorate, and if it is more than 1.4, impact resistance may decrease.
[0021] The propylene-based copolymer (A) and the propylene-based polymer (B) can be produced by the following method. The method for producing the propylene-based polymer (A) and the propylene-based polymer (B) used in the present invention is not particularly limited, but they are usually obtained by copolymerizing propylene and ethylene in the presence of a metallocene compound-containing catalyst or a Ziegler-Natta catalyst.
[0022] The propylene polymer (A) and the propylene polymer (B) are preferably obtained by copolymerizing propylene and ethylene in the presence of a Ziegler-Natta catalyst, because a resin having a broad molecular weight distribution and good moldability is easily obtained.
[0023] (Ziegler-Natta catalyst) The propylene polymer (A) and the propylene polymer (B) used in the present invention can be produced by using a highly stereoregular Ziegler-Natta catalyst. Various known catalysts can be used as the highly stereoregular Ziegler-Natta catalyst. For example, a catalyst can be used that is composed of (a) a solid titanium catalyst component that contains magnesium, titanium, a halogen, and an electron donor, (b) an organometallic compound catalyst component, and (c) an organosilicon compound catalyst component that has at least one group selected from the group consisting of a cyclopentyl group, a cyclopentenyl group, a cyclopentadienyl group, and derivatives thereof.
[0024] The solid titanium catalyst component (a) can be prepared by contacting a magnesium compound (a-1), a titanium compound (a-2) and an electron donor (a-3). The magnesium compound (a-1) can be a magnesium compound having reducing ability, such as a magnesium compound having a magnesium-carbon bond or a magnesium-hydrogen bond, or a magnesium compound having no reducing ability, such as magnesium halide, alkoxy magnesium halide, allyloxy magnesium halide, alkoxy magnesium, allyloxy magnesium, magnesium carboxylate, etc.
[0025] When preparing the solid titanium catalyst component (a), it is preferable to use, as the titanium compound (a-2), for example, a tetravalent titanium compound represented by the following formula (1). Ti(OR) g X 4-g …(1) (In formula (1), R is a hydrocarbon group, X is a halogen atom, and 0≦g≦4.)
[0026] Specifically, TiCl 4 , TiBr 4 , TiI 4 Titanium tetrahalides such as Ti(OCH 3 )Cl 3 , Ti(OC 2 H 5 )Cl 3 , Ti(OnC 4 H 9 )Cl 3 , Ti(OC 2 H 5 )Br 3 , Ti(O-iso-C 4 H 9 )Br 3 Alkoxy titanium trihalides such as Ti(OCH 3 ) 2 Cl 2 , Ti(OC 2 H 5 ) 2 Cl 2 , Ti(OnC 4 H 9 )2 Cl 2 , Ti(OC 2 H 5 ) 2 Br 2 Dihalogenated dialkoxy titanium such as Ti(OCH 3 ) 3 Cl, Ti(OC 2 H 5 ) 3 Cl, Ti(OnC 4 H 9 ) 3 Cl, Ti(OC 2 H 5 ) 3 Monohalogenated trialkoxy titanium such as Br; Ti(OCH 3 ) 4 , Ti(OC 2 H 5 ) 4 , Ti(OnC 4 H 9 ) 4 , Ti(O-iso-C 4 H 9 ) 4 , Ti(O-2-ethylhexyl) 4 and the like tetraalkoxytitanium.
[0027] Examples of the electron donor (a-3) used in preparing the solid titanium catalyst component (a) include alcohols, phenols, ketones, aldehydes, esters of organic or inorganic acids, organic acid halides, ethers, acid amides, acid anhydrides, ammonia, amines, nitriles, isocyanates, nitrogen-containing cyclic compounds, and oxygen-containing cyclic compounds.
[0028] When the magnesium compound (a-1), titanium compound (a-2) and electron donor (a-3) are contacted with each other, other reaction agents such as silicon, phosphorus and aluminum may be present, and a carrier may be used to prepare a carrier-supported solid titanium catalyst component (a).
[0029] The solid titanium catalyst component (a) can be prepared by employing any method, including known methods, and several examples will be briefly described below. (1) A method in which a hydrocarbon solution of a magnesium compound (a-1) containing an electron donor (liquefier) (a-3) is contacted with an organometallic compound to precipitate a solid, and then, while the solid is being precipitated, the solution is contacted with a titanium compound (a-2). (2) A method in which a complex consisting of a magnesium compound (a-1) and an electron donor (a-3) is contacted with an organometallic compound for reaction, and then a titanium compound (a-2) is contacted and reacted. (3) A method in which a contact product of an inorganic support and an organomagnesium compound (a-1) is contacted with a titanium compound (a-2) and an electron donor (a-3), in which the contact product may be contacted in advance with a halogen-containing compound and / or an organometallic compound. (4) A method in which a support carrying the magnesium compound (a-1) is obtained from a mixture of a solution of the magnesium compound (a-1) containing a liquefying agent and, in some cases, a hydrocarbon solvent, an electron donor (a-3) and a support, and then the support is contacted with a titanium compound (a-2). (5) A method of contacting a support with a solution containing a magnesium compound (a-1), a titanium compound (a-2), an electron donor (a-3), and optionally further a hydrocarbon solvent. (6) A method of contacting a liquid organomagnesium compound (a-1) with a halogen-containing titanium compound (a-2), using an electron donor (a-3) at least once. (7) A method in which a liquid organomagnesium compound (a-1) is contacted with a halogen-containing compound and then with a titanium compound (a-2), in which an electron donor (a-3) is used at least once during this process. (8) A method of contacting an alkoxy group-containing magnesium compound (a-1) with a halogen-containing titanium compound (a-2), using an electron donor (a-3) at least once. (9) A method of contacting a complex consisting of an alkoxy group-containing magnesium compound (a-1) and an electron donor (a-3) with a titanium compound (a-2). (10) A method in which a complex consisting of an alkoxy group-containing magnesium compound (a-1) and an electron donor (a-3) is contacted with an organometallic compound, and then contacted with a titanium compound (a-2) to cause a catalytic reaction. (11) A method of contacting and reacting a magnesium compound (a-1), an electron donor (a-3), and a titanium compound (a-2) in any order, in which, prior to this reaction, each component may be pretreated with a reaction aid such as an electron donor (a-3), an organometallic compound, or a halogen-containing silicon compound. (12) A method in which a liquid magnesium compound (a-1) having no reducing ability is reacted with a liquid titanium compound (a-2) in the presence of an electron donor (a-3) to precipitate a solid magnesium-titanium complex. (13) A method in which the reaction product obtained in the above (12) is further reacted with a titanium compound (a-2). (14) A method in which the reaction product obtained by the above (11) or (12) is further reacted with an electron donor (a-3) and a titanium compound (a-2). (15) A method for treating a solid obtained by grinding a magnesium compound (a-1), a titanium compound (a-2) and an electron donor (a-3) with any one of a halogen, a halogen compound or an aromatic hydrocarbon. This method may include a step of grinding only the magnesium compound (a-1), or a complex compound consisting of the magnesium compound (a-1) and the electron donor (a-3), or the magnesium compound (a-1) and the titanium compound (a-2). After grinding, the product may be pretreated with a reaction aid and then treated with a halogen or the like. As the reaction aid, an organometallic compound or a halogen-containing silicon compound or the like is used. (16) A method in which a magnesium compound (a-1) is pulverized and then contacted with a titanium compound (a-2), in which an electron donor (a-3) is used together with a reaction auxiliary, if necessary, during the pulverization and / or contact of the magnesium compound (a-1). (17) A method of treating the compounds obtained by any of the above (11) to (16) with a halogen, a halogen compound or an aromatic hydrocarbon. (18) A method of contacting a reaction product of a metal oxide, an organic magnesium (a-1) and a halogen-containing compound with an electron donor (a-3) and preferably a titanium compound (a-2). (19) A method of contacting a magnesium compound (a-1) such as a magnesium salt of an organic acid, an alkoxymagnesium, an aryloxymagnesium, etc. with a titanium compound (a-2), an electron donor (a-3) and, if necessary, a halogen-containing hydrocarbon. (20) A method of contacting a hydrocarbon solution containing a magnesium compound (a-1) and an alkoxytitanium with an electron donor (a-3) and, if necessary, a titanium compound (a-2). At this time, it is preferable to coexist a halogen-containing compound such as a halogen-containing silicon compound. (21) A method of reacting a liquid magnesium compound (a-1) having no reducing ability with an organometallic compound to precipitate a solid magnesium-metal (aluminum) composite, and then reacting an electron donor (a-3) and a titanium compound (a-2).
[0030] As the organometallic compound catalyst component (b), those containing a metal selected from Groups I to III of the periodic table are preferable. Specifically, examples include organoaluminum compounds as shown below, complex alkyl compounds of Group I metals and aluminum, and organometallic compounds of Group II metals.
[0031] Formula R 1 m Al(OR 2 ) n H p X q (In the formula, R 1 and R 2 are hydrocarbon groups usually containing 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms, and these may be the same or different from each other. X represents a halogen atom, 0 < m ≦ 3, n is a number of 0 ≦ n < 3, p is a number of 0 ≦ p < 3, q is a number of 0 ≦ q < 3, and m + n + p + q = 3.) An organoaluminum compound (b-1) represented by the formula.
[0032] Formula M 1 AlR1 4 (wherein M 1 is Li, Na or K, and R 1 is the same as described above.) The complex alkyl compound (b-2) of Group I metal and aluminum. Formula R 1 R 2 M 2 (wherein R 1 and R 2 are the same as above, and M 2 is Mg, Zn or Cd.) The dialkyl compound (b-3) of Group II or Group III.
[0033] Examples of the organoaluminum compound (b-1) include compounds represented by R 1 m Al(OR 2 ) 3-m (R 1 and R 2 are the same as above, and m is preferably a number of 1.5 ≦ m ≦ 3.), compounds represented by R 1 m AlX 3-m (R 1 is the same as above, X is halogen, and m is preferably 0 < m < 3.), compounds represented by R 1 m AlH 3-m (R 1 is the same as above, and m is preferably 2 ≦ m < 3.), compounds represented by R 1 m Al(OR 2 ) n X q (R 1 and R 2 are the same as above, X is halogen, 0 < m ≦ 3, 0 ≦ n < 3, 0 ≦ q < 3, and m + n + q = 3.), etc. can be mentioned.
[0034] Specific examples of the organosilicon compound catalyst component (c) include organosilicon compounds represented by the following formula (2). SiR 1 R 2 n(OR 3 ) 3-n …(2) (In formula (2), n is 0, 1 or 2; R 1 is a group selected from the group consisting of a cyclopentyl group, a cyclopentenyl group, a cyclopentadienyl group, and derivatives thereof; R 2 and R 3 represents a hydrocarbon group.)
[0035] In formula (2), R 1Specific examples of the cyclopentyl group include a cyclopentyl group, a 2-methylcyclopentyl group, a 3-methylcyclopentyl group, a 2-ethylcyclopentyl group, a 3-propylcyclopentyl group, a 3-isopropylcyclopentyl group, a 3-butylcyclopentyl group, a 3-tert-butylcyclopentyl group, a 2,2-dimethylcyclopentyl group, a 2,3-dimethylcyclopentyl group, a 2,5-dimethylcyclopentyl group, a 2,2,5-trimethylcyclopentyl group, a 2,3,4,5-tetramethylcyclopentyl group, a 2,2,5,5-tetramethylcyclopentyl group, a 1-cyclopentylpropyl group, a 1-methyl-1-cyclopentylethyl group, or a derivative thereof; a cyclopentenyl group, a 2-cyclopentenyl group, a 3-cyclopentenyl group, a 2-methyl-1-cyclopentenyl group, a 2-methyl-3-cyclopentenyl group, a 3-methyl-3-cyclopentenyl group, a 2-ethyl -3-cyclopentenyl group, 2,2-dimethyl-3-cyclopentenyl group, 2,5-dimethyl-3-cyclopentenyl group, 2,3,4,5-tetramethyl-3-cyclopentenyl group, 2,2,5,5-tetramethyl-3-cyclopentenyl group, or derivatives thereof; 1,3-cyclopentadienyl group, 2,4-cyclopentadienyl group, 1,4-cyclopentadienyl group, 2-methyl-1,3-cyclopentadienyl group, cyclopentadienyl groups or derivatives thereof, such as a 2-methyl-2,4-cyclopentadienyl group, a 3-methyl-2,4-cyclopentadienyl group, a 2-ethyl-2,4-cyclopentadienyl group, a 2,2-dimethyl-2,4-cyclopentadienyl group, a 2,3-dimethyl-2,4-cyclopentadienyl group, a 2,5-dimethyl-2,4-cyclopentadienyl group, or a 2,3,4,5-tetramethyl-2,4-cyclopentadienyl group;Further, examples of derivatives of a cyclopentyl group, a cyclopentenyl group, or a cyclopentadienyl group include an indenyl group, a 2-methylindenyl group, a 2-ethylindenyl group, a 2-indenyl group, a 1-methyl-2-indenyl group, a 1,3-dimethyl-2-indenyl group, an indanyl group, a 2-methylindanyl group, a 2-indanyl group, a 1,3-dimethyl-2-indanyl group, a 4,5,6,7-tetrahydroindenyl group, a 4,5,6,7-tetrahydro-2-indenyl group, a 4,5,6,7-tetrahydro-1-methyl-2-indenyl group, a 4,5,6,7-tetrahydro-1,3-dimethyl-2-indenyl group, and a fluorenyl group.
[0036] In addition, in formula (2), R 2 and R 3 Specific examples of the hydrocarbon group include an alkyl group, a cycloalkyl group, an aryl group, and an aralkyl group. 2 or R 3 If there are two or more, R 2 Peer or R 3 may be the same or different, and R 2 and R 3 may be the same or different. In formula (2), R 1 and R 2 may be crosslinked with an alkylene group or the like.
[0037] Among the organosilicon compounds represented by formula (2), R 1 is a cyclopentyl group, and R 2 is an alkyl group or a cyclopentyl group, and R 3 Preferred are organosilicon compounds in which R is an alkyl group, particularly a methyl or ethyl group.
[0038] Specific examples of the organosilicon compound represented by formula (2) include trialkoxysilanes such as cyclopentyltrimethoxysilane, 2-methylcyclopentyltrimethoxysilane, 2,3-dimethylcyclopentyltrimethoxysilane, 2,5-dimethylcyclopentyltrimethoxysilane, cyclopentyltriethoxysilane, cyclopentenyltrimethoxysilane, 3-cyclopentenyltrimethoxysilane, 2,4-cyclopentadienyltrimethoxysilane, indenyltrimethoxysilane, and fluorenyltrimethoxysilane; dicyclopentyldimethoxysilane, bis(2-methylcyclopentyl)dimethoxysilane, bis(3-tert-butylcyclopentyl)dimethoxysilane, bis(2,3-dimethylcyclopentyl)dimethoxysilane, and bis(2,5-dimethylcyclopentyl)dimethoxysilane; Dicyclopentyldiethoxysilane, dicyclopentenyldimethoxysilane, di(3-cyclopentenyl)dimethoxysilane, bis(2,5-dimethyl-3-cyclopentenyl)dimethoxysilane, di-2,4-cyclopentadienyldimethoxysilane, bis(2,5-dimethyl-2,4-cyclopentadienyl)dimethoxysilane, bis(1-methyl-1-cyclopentylethyl)dimethoxysilane, cyclopentylcyclopentenyldimethoxysilane, cyclopentylcyclopentadienyldimethoxysilane, diindenyldimethoxysilane, bis(1,3-dimethyl-2-indenyl)dimethoxysilane, cyclopentadienylindenyldimethoxysilane, difluorenyldimethoxysilane, cyclopentylfluorenyldimethoxysilane, indenylfluorenyldimethoxysilane and other dialkoxysilanes;Monoalkoxysilanes such as tricyclopentyl methoxysilane, tricyclopentenyl methoxysilane, tricyclopentadienyl methoxysilane, tricyclopentyl ethoxysilane, dicyclopentyl methyl methoxysilane, dicyclopentyl ethyl methoxysilane, dicyclopentyl methyl ethoxysilane, cyclopentyl dimethyl methoxysilane, cyclopentyl diethyl methoxysilane, cyclopentyl dimethyl ethoxysilane, bis(2,5-dimethylcyclopentyl)cyclopentyl methoxysilane, dicyclopentyl cyclopentenyl methoxysilane, dicyclopentyl cyclopentadienyl methoxysilane, and diindenyl cyclopentyl methoxysilane; and other monoalkoxysilanes such as ethylene biscyclopentyl dimethoxysilane.
[0039] When propylene is polymerized using a catalyst comprising the above-mentioned solid titanium catalyst component (a), organometallic compound catalyst component (b), and organosilicon compound catalyst component (c), a prepolymerization can be carried out in advance. In the prepolymerization, olefins are polymerized in the presence of the solid titanium catalyst component (a), the organometallic compound catalyst component (b), and, if necessary, the organosilicon compound catalyst component (c).
[0040] As the prepolymerized olefin, an α-olefin having 2 to 8 carbon atoms can be used. Specifically, linear olefins such as ethylene, propylene, 1-butene, and 1-octene; olefins having a branched structure such as 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene can be used. These may be copolymerized.
[0041] The prepolymerization is desirably carried out so that about 0.1 to 1000 g, preferably about 0.3 to 500 g of polymer is produced per 1 g of the solid titanium catalyst component (a). If the amount of prepolymerization is too large, the efficiency of producing the (co)polymer in the main polymerization may decrease. In the prepolymerization, the catalyst can be used at a concentration considerably higher than the catalyst concentration in the system in the main polymerization. When propylene is continuously polymerized in multiple stages using the above catalyst, propylene and ethylene may be copolymerized in any or all stages within a range that does not impair the object of the present invention.
[0042] In the case of continuous multi-stage polymerization, polypropylene is produced in each stage by homopolymerizing propylene or copolymerizing propylene and ethylene. In the main polymerization, it is desirable to use the solid titanium catalyst component (a) (or prepolymerization catalyst) in an amount of about 0.0001 to 50 millimoles, preferably about 0.001 to 10 millimoles, calculated as titanium atoms per 1 L of polymerization volume. It is desirable to use the organometallic compound catalyst component (b) in an amount of about 1 to 2000 moles, preferably about 2 to 500 moles, in terms of the amount of metal atoms per mole of titanium atoms in the polymerization system. It is desirable to use the organosilicon compound catalyst component (c) in an amount of about 0.001 to 50 moles, preferably about 0.01 to 20 moles, per mole of metal atoms of the organometallic compound catalyst component (b).
[0043] (Production method of propylene polymer (A)) The propylene polymer (A) used in the present invention can be obtained by copolymerizing propylene and ethylene in the presence of the above-mentioned metallocene compound-containing catalyst or Ziegler-Natta catalyst.
[0044] The polymerization may be carried out by any of gas phase polymerization method or liquid phase polymerization method such as solution polymerization method or suspension polymerization method, and each stage may be carried out by a different method. The polymerization may be carried out by any of continuous and semi-continuous methods, and each stage may be carried out by dividing it into a plurality of polymerization vessels, for example, 2 to 10 polymerization vessels. From an industrial perspective, polymerization by a continuous method is most preferable, and in this case, polymerization from the second stage onwards is preferably carried out by dividing it into two or more polymerization vessels, which can suppress the generation of high molecular weight components, which are by-products called gels that have undesirable negative effects on impact resistance and transparency.
[0045] As the polymerization medium, an inert hydrocarbon may be used, or liquid propylene may be used. The polymerization conditions for each stage are appropriately selected such that the polymerization temperature is within the range of about -50 to +200°C, preferably about 20 to 100°C, and the polymerization pressure is within the range of normal pressure to 10 MPa (gauge pressure), preferably about 0.2 to 5 MPa (gauge pressure).
[0046] In producing the propylene polymer (A), the following [Step 1] is carried out. In [Step 1], propylene and a required amount of ethylene are copolymerized at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure. In [Step 1], the amount of ethylene fed is made small relative to propylene so that the propylene-based copolymer produced in [Step 1] satisfies the requirement (A1). In addition, a chain transfer agent such as hydrogen gas is also introduced as necessary to adjust the intrinsic viscosity [η] of the propylene-based copolymer produced in [Step 1] so that the propylene-based copolymer produced in [Step 1] satisfies the requirement (A2).
[0047] Requirement (A1) can be adjusted by adjusting the amount of propylene and the amount of ethylene fed when carrying out [Step 1]. That is, by increasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the polypropylene copolymer (A) can be increased. In addition, by decreasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the polypropylene copolymer (A) can be decreased.
[0048] Requirement (A2) can be adjusted by the feed amount of hydrogen gas used as a chain transfer agent in carrying out [Step 1]. In other words, the intrinsic viscosity [η] can be reduced by increasing the feed amount of hydrogen gas relative to the feed amount of propylene or, in the case of feeding propylene and ethylene, the feed amount of propylene and ethylene. Conversely, the intrinsic viscosity [η] can be increased by decreasing the feed amount of hydrogen gas relative to the feed amount of propylene or, in the case of feeding propylene and ethylene, the feed amount of propylene and ethylene. After the polymerization is completed, known post-treatment steps such as a catalyst deactivation step, a catalyst residue removal step, and a drying step are carried out as necessary, to obtain the propylene-based copolymer (A) as a powder.
[0049] (Method for producing propylene polymer (B)) The propylene polymer (B) used in the present invention can be obtained by copolymerizing propylene and ethylene in the presence of the above-mentioned metallocene compound-containing catalyst or Ziegler-Natta catalyst.
[0050] The polymerization may be carried out by any of gas phase polymerization method or liquid phase polymerization method such as solution polymerization method or suspension polymerization method, and each stage may be carried out by a different method. The polymerization may be carried out by any of continuous and semi-continuous methods, and each stage may be carried out by dividing it into a plurality of polymerization vessels, for example, 2 to 10 polymerization vessels. From an industrial perspective, polymerization by a continuous method is most preferable, and in this case, polymerization from the second stage onwards is preferably carried out by dividing it into two or more polymerization vessels, which can suppress the generation of high molecular weight components, which are by-products called gels that have undesirable negative effects on impact resistance and transparency.
[0051] As the polymerization medium, an inert hydrocarbon may be used, or liquid propylene may be used. The polymerization conditions for each stage are appropriately selected such that the polymerization temperature is within the range of about -50 to +200°C, preferably about 20 to 100°C, and the polymerization pressure is within the range of normal pressure to 10 MPa (gauge pressure), preferably about 0.2 to 5 MPa (gauge pressure).
[0052] In the case of producing the propylene polymer (B), the following [Step 2] is carried out. In [Step 2], propylene and a required amount of ethylene are copolymerized at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure. In [Step 2], the amount of ethylene fed is made small relative to propylene so that the propylene-based copolymer produced in [Step 2] satisfies the requirement (B1). In addition, a chain transfer agent such as hydrogen gas is also introduced as necessary to adjust the intrinsic viscosity [η] of the propylene-based copolymer produced in [Step 2] so that the propylene-based copolymer produced in [Step 2] satisfies the requirement (B2).
[0053] Requirement (B1) can be adjusted by adjusting the amount of propylene and the amount of ethylene fed in [Step 2]. That is, by increasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the polypropylene copolymer (B) can be increased. Also, by decreasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the polypropylene copolymer (B) can be decreased.
[0054] Requirement (B2) can be adjusted by the feed amount of hydrogen gas used as a chain transfer agent in carrying out [Step 2]. In other words, the intrinsic viscosity [η] can be reduced by increasing the feed amount of hydrogen gas relative to the feed amount of propylene or, in the case of feeding propylene and ethylene, the feed amount of propylene and ethylene. Conversely, the intrinsic viscosity [η] can be increased by decreasing the feed amount of hydrogen gas relative to the feed amount of propylene or, in the case of feeding propylene and ethylene, the feed amount of propylene and ethylene. After the polymerization is completed, known post-treatment steps such as a catalyst deactivation step, a catalyst residue removal step, and a drying step are carried out as necessary, to obtain the propylene-based copolymer (B) as a powder.
[0055] Alternatively, a propylene polymer may be obtained by continuously carrying out two steps ([Step 1] and [Step 2]) in a reaction apparatus in which two or more polymerization vessels are connected in series. In this case, the propylene polymer obtained in [Step 1] is a propylene polymer (A), and the propylene polymer obtained in [Step 2] is a propylene polymer (B).
[0056] When two steps ([Step 1] and [Step 2]) are carried out consecutively, a polymerization apparatus having two or more reactors connected in series can be used to carry out [Step 1] in each polymerization apparatus, and a polymerization apparatus having two or more reactors connected in series can be used to carry out [Step 2] in each polymerization apparatus.
[0057] Requirements (A1), (A2), (B1) and (B2) can be reconciled as follows: The requirements (A1) and (B1) can be adjusted by adjusting the amount of propylene and the amount of ethylene fed when carrying out [Step 1] and [Step 2]. That is, by increasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the propylene-based copolymer can be increased. Also, by decreasing the amount of ethylene fed relative to the amount of propylene fed, the mass of the structural units derived from ethylene in the propylene-based copolymer can be decreased.
[0058] The requirements (A2) and (B2) can be adjusted by adjusting the feed amount of hydrogen gas as a chain transfer agent relative to the feed amount of propylene when performing [Step 1] and [Step 2], or relative to the feed amounts of propylene and ethylene when feeding propylene and ethylene. The intrinsic viscosity [η] can be lowered by increasing the feed amount of hydrogen relative to the feed amounts of propylene and ethylene when feeding propylene or propylene and ethylene, and the intrinsic viscosity [η] can be increased by decreasing the feed amount of hydrogen relative to the feed amounts of propylene or propylene and ethylene when feeding propylene or propylene and ethylene.
[0059] As the propylene copolymer (A) and the propylene-based copolymer (B), commercially available existing products can be used. When two steps ([Step 1] and [Step 2]) are carried out consecutively, the ratio of polypropylene copolymer (A) to polypropylene copolymer (B) can be adjusted by adjusting the polymerization times of the above [Step 1] and [Step 2]. In other words, by making the polymerization time of the above [Step 1] longer than that of [Step 2], the ratio of propylene copolymer (A) can be increased and the ratio of propylene copolymer (B) can be decreased. Also, by making the polymerization time of [Step 2] longer than that of [Step 1], the ratio of propylene copolymer (A) can be decreased and the ratio of propylene copolymer (B) can be increased.
[0060] The nucleating agent (D) is not particularly limited, and examples thereof include carboxylate metal salt-based nucleating agents such as aluminum para-tertiary butyl benzoate and sodium benzoate, sorbitol-based nucleating agents such as dibenzylidene sorbitol and di-alkyl-benzylidene sorbitol, and phosphate metal salt-based nucleating agents such as sodium phosphate, etc. Among these, phosphate metal salt nucleating agents such as ADK STAB NA11 (manufactured by ADEKA CORPORATION) and carboxylate metal salt-based nucleating agents such as AL-PTBBA (manufactured by Dainippon Ink and Chemicals, Inc.) can be preferably used.
[0061] In the polypropylene resin composition of the present invention, the content ratios of the propylene copolymer (A), the propylene copolymer (B) and the nucleating agent (D) are 80-90 parts by mass of the propylene copolymer (A), 10-20 parts by mass of the propylene copolymer (B), and 0.01-0.6 parts by mass of the nucleating agent (D), where the total of the propylene copolymer (A) and the propylene copolymer (B) is 100 parts by mass. The content ratio of the propylene copolymer (A) is preferably 81-89 parts by mass, more preferably 82-88 parts by mass. The content ratio of the propylene copolymer (B) is preferably 11-19 parts by mass, more preferably 12-18 parts by mass. The content ratio of the nucleating agent (D) is preferably 0.03-0.3 parts by mass, more preferably 0.05-0.2 parts by mass.
[0062] When the content ratio of the propylene-based copolymer (A), the propylene-based copolymer (B) and the nucleating agent (D) is within the above range, a polypropylene-based resin composition having both whitening resistance and impact resistance can be obtained.
[0063] The polypropylene resin composition may further contain additives such as pigments, vitamins, antioxidants, heat stabilizers, weather stabilizers, slip agents, antiblocking agents, petroleum resins, and mineral oils, as necessary, within the scope of the object of the present invention.
[0064] The polypropylene resin composition of the present invention satisfies the following requirement (C1). (C1) The melt flow rate (MFR) measured in accordance with JIS K 7210 at 230°C under a load of 2.16 kg is 10 to 50 g / 10 min.
[0065] The polypropylene resin composition of the present invention has a melt flow rate (MFR) measured in accordance with JIS K 7210 at 230°C under a load of 2.16 kg of 10 to 50 g / 10 min, preferably 15 to 50 g / 10 min, and more preferably 20 to 50 g / 10 min.
[0066] When the polypropylene resin composition of the present invention has a melt flow rate of less than 10, the orientation at the hinge portion during injection becomes strong, and peeling and whitening easily occur. When the melt flow rate is more than 50, the orientation at the hinge portion during injection becomes weak, and deformation easily occurs.
[0067] The polypropylene resin composition of the present invention contains the propylene copolymer (A), the propylene copolymer (B) and the nucleating agent (D) in the above-mentioned content ratio and satisfies the above-mentioned requirement (C1), thereby achieving both whitening resistance and impact resistance of the hinge portion in applications such as bottle caps. The reason for obtaining such an effect is presumed to be as follows.
[0068] By reducing the difference in intrinsic viscosity between the propylene-based copolymer (A) and the propylene-based copolymer (B), the dispersed particle size can be appropriately controlled and peeling at the interface between the two components due to bending at the hinge portion or impact can be suppressed, resulting in improved whitening resistance and impact resistance.
[0069] The propylene-based copolymer (A) contains an appropriate ratio of structural units derived from ethylene, which improves the interfacial strength with the propylene-based copolymer (B) and provides flexibility, thereby satisfying the requirements for the cap to adhere to the bottle portion and to seal the contents when the cap is closed.
[0070] If the above conditions are satisfied, the material will become too flexible, resulting in a drawback of weak opening and closing torque. However, by adding a nucleating agent to strengthen the orientation layer on the product surface, the tensile modulus is improved and the opening and closing torque can be optimized.
[0071] It is preferable that the polypropylene resin composition of the present invention further satisfies the following requirements (C2) to (C4). (C2) The tensile modulus measured in accordance with JIS K 7161 is 800 to 900 MPa. The polypropylene resin composition of the present invention preferably has a tensile modulus measured in accordance with JIS K 7161 of 800 to 900 MPa. When the polypropylene resin composition of the present invention has a tensile modulus of elasticity of less than 800 MPa, it is prone to deformation, and when it has a tensile modulus of elasticity of more than 900 MPa, it is prone to peeling and whitening.
[0072] (C3) The total energy of high-speed surface impact measured in a 0°C environment in accordance with the ASTM D 3763-02 high-speed impact test method is 20 J or more. The polypropylene resin composition of the present invention preferably has a high-speed surface impact total energy of 20 J or more, as measured in a 0° C. environment in accordance with the high-speed impact test method of ASTM D 3763-02. When the high-speed surface impact total energy of the polypropylene resin composition of the present invention is less than 20 J, the impact resistance tends to be insufficient.
[0073] (C4) A hard ball is dropped onto the center of a test piece obtained by injection molding, and the change in L value in L / a / b at the center of the test piece measured before and after the drop is Δ10 or less. The polypropylene resin composition of the present invention is preferably such that a change in L value ΔL in L / a / b at the center of a test piece obtained by injection molding is measured before and after a hard ball is dropped onto the center of the test piece, and the change is 10 or less.
[0074] When the polypropylene resin composition of the present invention has a ΔL of more than 10, the whitening resistance tends to be insufficient. The method for producing the polypropylene-based resin composition used in the present invention is not particularly limited. For example, the propylene-based copolymer (A), the propylene-based copolymer (B), the nucleating agent (D), and various other components used as necessary can be blended in a mixer such as a Henschel mixer, a Banbury mixer, or a tumbler mixer, and then kneaded in a single-screw or twin-screw extruder to obtain a pellet-shaped composition.
[0075] The composition satisfying the above requirements (C1) to (C4) can be produced with reference to the method described in the Examples below.
[0076] [Molded body] The molded article of the present invention contains the polypropylene resin composition. The molded article of the present invention can be obtained by molding the polypropylene resin composition by various molding methods. As described above, the polypropylene resin composition has excellent whitening resistance and impact resistance, so it can be used for various molded articles, and can be particularly preferably used for bottle caps having hinge parts.
[0077] Bottle caps having a hinge portion are particularly susceptible to whitening at the hinge portion which is repeatedly bent and curved. However, a bottle cap containing the polypropylene-based resin composition of the present invention is less susceptible to whitening even at the hinge portion and also has high impact resistance.
[0078] The method for molding the bottle cap is not particularly limited, but injection molding or compression molding is usually adopted. EXAMPLES
[0079] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples. The methods for measuring physical properties in the examples and comparative examples are as follows.
[0080] (Content of structural units derived from ethylene) The weight of the structural unit derived from ethylene in the propylene polymer (A) and the propylene polymer (B) is 13 It was determined by measurement and calculation as follows based on the CNMR measurement. 13 C-NMR measurement conditions Measurement equipment: JEOL LA400 type nuclear magnetic resonance spectrometer Measurement mode: BCM (Bilevel Complete decoupling) Observation frequency: 100.4MHz Observation range: 17006.8Hz Pulse width: C core 45° (7.8 μsec) Pulse repetition time: 5 seconds Sample tube: 5mmφ Sample tube rotation speed: 12Hz Accumulation count: 20,000 times Measurement temperature: 125℃ Solvent: 1,2,4-trichlorobenzene: 0.35 ml / heavy benzene: 0.2 ml Sample size: approx. 40 mg
[0081] From the spectrum obtained by the measurement, the ratio of monomer sequence distribution (triad distribution) was determined according to the following literature (1), and the molar fraction (mol%) of the ethylene-derived structural unit of the propylene-based polymer (hereinafter referred to as E (mol%)) and the molar fraction (mol%) of the propylene-derived structural unit (hereinafter referred to as P (mol%)) were calculated. The weight (weight%) of the ethylene-derived structural unit in the Dsol of the propylene-based polymer (hereinafter referred to as E (wt%)) was calculated by converting the calculated E (mol%) and P (mol%) into weight% according to the following (Equation 1).
[0082] References (1): Kakugo, M.; Naito, Y.; Mizunuma, K.; Miyatake, T., Carbon-13 NMR determination of ation of monomer sequence distribution in ethylene-propylene copolymers prepared with delta-titanium trichloride-diethylaluminum chloride. Macromolecules 1982, 15, (4), 1150-1152 E(wt%)=E(mol%)×28×100 / [P(mol%)×42+E(mol%)×28] (Formula 1)
[0083] (Intrinsic viscosity [η]) The measurement was performed at 135°C using decalin as a solvent. Approximately 20 mg of the sample was dissolved in 15 ml of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 ml of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity. [η] = lim(η sp / C) (C→0).
[0084] (Melt Flow Rate (MFR)) The melt flow rate was measured in accordance with JIS K 7210 at 230° C. under a load of 2.16 kg.
[0085] (tensile modulus) The tensile modulus was measured in accordance with JIS K 7161 using a type A test piece.
[0086] (High-velocity surface impact total energy) A polypropylene resin composition was injection molded to prepare a test piece having a length of 129 mm, a width of 119 mm, and a thickness of 2 mm. The high-speed surface impact total energy was measured using this test piece in a 0°C environment in accordance with the ASTM D 3763-02 high-speed impact test method.
[0087] (Impact whitening resistance) Using the same test piece as that used in the measurement of the total energy of high-speed surface impact, a hard ball weighing 95.1 g and having a diameter of 28.6 mm was dropped from a height of 20 cm onto the center of the test piece. The L value in L / a / b at the center of the test piece was measured before and after the drop, and the change in L value after the drop from the L value before the drop was calculated as the L value change ΔL.
[0088] (Hinge performance) A polypropylene resin composition was injection molded to prepare a test piece having a length of 80 mm, a width of 20 mm, and a thickness of 2 mm, with a hinge part having a length of 0.4 mm (3 mm including the tapered part from the test piece), a thickness of 0.2 mm, and a width of 14 mm. A test was conducted in which the test piece was repeatedly bent 90° at the hinge part 100,000 times. The deformation property, peel resistance, and whitening property of the hinge part were evaluated according to the following criteria.
[0089] Deformability After the test, the dimensions of the hinge portion were measured to determine the change from the original dimensions of the hinge portion, and the deformability of the hinge portion was evaluated according to the following criteria. ◯: The change in dimension of the hinge portion from the original dimension was 0.05 mm or less. ×: The change in dimension of the hinge portion from the original dimension was more than 0.05 mm.
[0090] ·Peeling resistance After the test, the condition of the hinge portion was visually observed, and the peel resistance of the hinge portion was evaluated according to the following criteria. ◯: There was no change in shape due to peeling on the surface of the hinge part. ×: The surface of the hinge part was changed in shape due to peeling.
[0091] ·Whitening property After the test, the condition of the hinge portion was visually observed, and the degree of whitening of the hinge portion was evaluated according to the following criteria. ◯: No whitening was observed in the hinge area. ×: Whitening was observed at the hinge portion.
[0092] The polymers used in the examples and comparative examples are as follows. [Production Example 1] (Production of Propylene-Based Copolymer (A-1)) (1) Preparation of solid catalyst component 95.2 g of anhydrous magnesium chloride, 442 ml of decane, and 390.6 g of 2-ethylhexyl alcohol were reacted by heating at 130°C for 2 hours to obtain a homogeneous solution, and then 21.3 g of phthalic anhydride was added to this solution, followed by stirring and mixing at 130°C for 1 hour to dissolve the phthalic anhydride.
[0093] The homogeneous solution thus obtained was cooled to room temperature, and then 75 ml of this homogeneous solution was added dropwise over one hour to 200 ml of titanium tetrachloride kept at -20° C. After the addition was completed, the temperature of this mixture was raised to 110° C. over four hours, and when it reached 110° C., 5.22 g of diisobutyl phthalate (DIBP) was added, and the mixture was stirred and kept at the same temperature for another two hours.
[0094] After the 2-hour reaction, the solid was collected by hot filtration, resuspended in 275 ml of titanium tetrachloride, and then heated again for 2 hours at 110° C. After the reaction was completed, the solid was collected again by hot filtration and thoroughly washed with decane and hexane at 110° C. until no free titanium compounds were detected in the solution.
[0095] Here, the detection of the free titanium compounds was confirmed by the following method. 10 ml of the supernatant of the solid catalyst component was taken with a syringe and placed in a 100 ml sidearm Schlenk tube that had been previously purged with nitrogen. Next, the solvent hexane was dried using a nitrogen stream, and then vacuum dried for a further 30 minutes. 40 ml of ion-exchanged water and 10 ml of 50% by volume sulfuric acid were added to the solution, and the mixture was stirred for 30 minutes. This aqueous solution was transferred to a 100 ml measuring flask through filter paper, and then conc. H was added as a masking agent for iron (II) ions. 3 PO 4 1ml and 3% H as a coloring reagent for titanium 2 O 2 5 ml of the aqueous solution was added, and the volume was increased to 100 ml with ion-exchanged water. The measuring flask was shaken, and after 20 minutes, the absorbance at 420 nm was observed using UV to detect free titanium. The free titanium was washed away and detected until the absorbance was no longer observed.
[0096] The solid titanium catalyst component (A) prepared as above was stored as a decane slurry, and a part of it was dried for the purpose of examining the catalyst composition. The composition of the solid titanium catalyst component (A) thus obtained was 2.3 mass% titanium, 61 mass% chlorine, 19 mass% magnesium, and 12.5 mass% DIBP.
[0097] (2) Preparation of prepolymerized catalyst component After replacing the inside of a 500 ml three-necked flask equipped with a stirrer with nitrogen gas, 400 ml of dehydrated heptane, 19.2 mmol of triethylaluminum, 3.8 mmol of dicyclopentyldimethoxysilane, and 4 g of the above solid titanium catalyst component (A) were added. The internal temperature was kept at 20°C, and propylene was introduced while stirring. After 1 hour, the stirring was stopped, and as a result, a prepolymerized catalyst component (B) was obtained in which 2 g of propylene was polymerized per 1 g of the solid titanium catalyst component (A).
[0098] Polymerization [Step 1] A stainless steel autoclave with a stirrer and a capacity of 10 L was thoroughly dried and purged with nitrogen, after which 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was purged with propylene, hydrogen was charged at 0.80 MPa-G, and then propylene and ethylene were introduced with stirring. The amount of introduction was adjusted so that the ethylene concentration in the gas phase in the polymerization tank was 0.80 mol%.
[0099] After the system was stabilized at an internal temperature of 80°C and a total pressure of 0.8 MPa-G, 20.8 ml of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 3 hours while continuously supplying propylene.
[0100] After a predetermined time had elapsed, 50 ml of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter, and the temperature was raised to 60°C to separate the solid and liquid. The solid portion was further washed twice with 6 L of heptane at 60°C. The resulting propylene / ethylene copolymer was vacuum dried to obtain a propylene-based copolymer (A-1). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting propylene-based copolymer (A-1).
[0101] [Production Example 2] (Production of Propylene-Based Copolymer (A-2)) In the production of the propylene-based copolymer (A-1), the hydrogen charging amount in the polymerization [step 1] was set to 0.75 MPa-G, and the ethylene concentration in the gas phase in the polymerization tank was adjusted to 0.55 mol%, but the polymerization was carried out in the same manner as in the production of the propylene-based copolymer (A-1), to obtain a propylene-based copolymer (A-2). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting propylene-based copolymer (A-2).
[0102] [Production Example 3] (Production of Polymer (a-1)) In the production of the propylene-based copolymer (A-1), the polymerization was carried out in the same manner as in the production of the propylene-based copolymer (A-1), except that the hydrogen charging amount in the polymerization [step 1] was set to 0.75 MPa-G and the ethylene concentration in the gas phase in the polymerization tank was adjusted to 1.45 mol%, to obtain a polymer (a-1). The content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting polymer (a-1) are shown in Table 1.
[0103] [Production Example 4] (Production of Polymer (a-2)) In the production of the propylene-based copolymer (A-1), polymerization was carried out in the same manner as in the production of the propylene-based copolymer (A-1), except that the ethylene concentration in the gas phase in the polymerization tank in the polymerization [step 1] was adjusted to 1.40 mol%, to obtain a polymer (a-2). The content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting polymer (a-2) are shown in Table 1.
[0104] [Production Example 5] (Production of polymer (a-3)) In the production of the propylene-based copolymer (A-1), polymerization was carried out in the same manner as in the production of the propylene-based copolymer (A-1), except that ethylene was not introduced into the polymerization tank in the polymerization [step 1], to obtain a polymer (a-3). The content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting polymer (a-3) are shown in Table 1.
[0105] [Production Example 6] (Production of Propylene-Based Copolymer (B-1)) Polymerization [Step 2] A stainless steel autoclave with a stirrer and a capacity of 10 L was thoroughly dried and purged with nitrogen, and then 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was purged with propylene, 20.8 ml of heptane slurry containing 0.10 mmol of the above prepolymerized catalyst component (B) in terms of Ti atom was added, and hydrogen was charged at 1.70 MPa-G, followed by the introduction of a mixed gas of propylene / ethylene: (4.0 L / min) / (2.32 / min). Propylene / ethylene copolymerization was carried out for 60 minutes at an internal temperature of 60°C and a total pressure of 0.30 MPa-G (varies depending on the amount of gas introduced).
[0106] After a predetermined time had elapsed, 50 ml of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter, and the temperature was raised to 60°C to separate the solid and liquid. Furthermore, the solid portion was washed twice with 6 L of heptane at 60°C. The resulting propylene / ethylene copolymer was vacuum dried to obtain a propylene-based copolymer (B-1). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting propylene-based copolymer (B-1).
[0107] [Production Example 7] (Production of Propylene Copolymer (B-2)) The polymerization was carried out in the same manner as in the production of the propylene-based copolymer (B-1), except that a mixed gas of propylene / ethylene: (4.0 l / min) / (1.20 l / min) was introduced after hydrogen insertion, to obtain a propylene-based copolymer (B-2). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting propylene-based copolymer (B-2).
[0108] [Production Example 8] (Production of polymer (b-1)) In the production of the propylene copolymer (B-1), polymerization was carried out in the same manner as in the production of the propylene copolymer (B-1), except that hydrogen was charged at 1.60 MPa-G and a mixed gas of propylene / ethylene: (4.0 l / min) / (0.72 / min) was introduced, to obtain a polymer (b-1). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting polymer (b-1).
[0109] [Production Example 9] (Production of polymer (b-2)) Polymerization was carried out in the same manner as in the production of the propylene-based copolymer (B-1), except that hydrogen was charged at 0.20 MPa-G and a mixed gas of propylene / ethylene: (4.0 l / min) / (2.49 / min) was introduced, to obtain polymer (b-2). Table 1 shows the content of structural units derived from ethylene and the intrinsic viscosity [η] of the resulting polymer (b-2).
[0110] Polymer (b-3): Mitsui Chemicals, Inc., Hi-Zex 2200J (MFR: 5.2 g / 10 min, density: 964 kg / m 3 ) Polymer (b-4): Evolu S P1540 manufactured by Prime Polymer Co., Ltd. (MFR: 3.8 g / 10 min, density: 913 kg / m 3 ) Polymer (b-5): Evolu P SP00206 manufactured by Prime Polymer Co., Ltd. (MFR: 18.0 g / 10 min, density: 900 kg / m 3 )
[0111] [Example 1] The propylene-based copolymer (A-1), the propylene-based copolymer (B-1) and ADK STAB NA11 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene-based resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0112] [Example 2] The propylene-based copolymer (A-2), the propylene-based copolymer (B-2) and AL-PTBBA as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene-based resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0113] [Comparative Example 1] The propylene-based copolymer (A-1) and the propylene-based copolymer (B-1) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene-based resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0114] [Comparative Example 2] The propylene-based copolymer (a-1), the propylene-based copolymer (b-1) and ADK STAB NA21 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene-based resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0115] [Comparative Example 3] The propylene copolymer (a-1), the polymer (b-3) and ADK STAB NA11 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0116] [Comparative Example 4] The propylene copolymer (a-2), the polymer (b-4) and ADK STAB NA21 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0117] [Comparative Example 5] The propylene-based copolymer (a-3), the propylene-based copolymer (b-2), and AL-PTBBA as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene-based resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0118] [Comparative Example 6] The propylene copolymer (a-2), the polymer (b-5) and ADK STAB NA21 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene resin composition. The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0119] [Comparative Example 7] The propylene copolymer (a-2) and ADK STAB NA21 as the nucleating agent (D) were mixed in the amounts shown in Table 1, and melt-kneaded in an extruder to prepare a polypropylene resin composition.
[0120] The melt flow rate and tensile modulus of the resulting polypropylene resin composition were determined by the above-mentioned methods, and the results are shown in Table 1. Furthermore, the high-speed surface impact total energy, L value change ΔL, and hinge performance were determined by the above-mentioned methods using the obtained polypropylene resin composition. The results are shown in Table 1.
[0121] [Table 1]
Claims
1. The composition comprises 80 to 90 parts by mass of a propylene-based copolymer (A) satisfying the following requirements (A1) and (A2), 10 to 20 parts by mass of a propylene-based copolymer (B) satisfying the following requirements (B1) and (B2), and 0.01 to 0.6 parts by mass of a nucleating agent (D) (wherein the total of the propylene-based copolymer (A) and the propylene-based copolymer (B) is 100 parts by mass); the nucleating agent (D) is at least one selected from the group consisting of a metal carboxylate nucleating agent and a metal phosphate nucleating agent, A polypropylene resin composition satisfying the following requirement (C1): (A1) The content of structural units derived from ethylene in the propylene-based copolymer (A) is 1.0 to 3.0% by mass. (A2) Intrinsic viscosity [η] of propylene copolymer (A) in decalin at 135°C (A) is 1.0 to 2.0 dl / g. (B1) The content of structural units derived from ethylene in the propylene-based copolymer (B) is 20 to 40 mass %. (B2) Intrinsic viscosity [η] of propylene copolymer (B) in decalin at 135 ° C. (B) is 1.0 to 2.0 dl / g, and the intrinsic viscosity ratio [η] of the propylene-based copolymer (B) / propylene-based copolymer (A) is (B) / [η] (A) is 0.8 to 1.
4. (C1) The melt flow rate (MFR), measured in accordance with JIS K 7210 at 230° C. under a load of 2.16 kg, is 10 to 50 g / 10 min.
2. The polypropylene resin composition according to claim 1, further satisfying the following requirements (C2) to (C4): (C2) The tensile modulus, measured in accordance with JIS K 7161, is 800 to 900 MPa. (C3) The total energy of a high-speed surface impact measured in a 0°C environment in accordance with the ASTM D 3763-02 high-speed impact test method is 20 J or more. (C4) A hard ball is dropped onto the center of a test piece obtained by injection molding, and the change in L value ΔL in L / a / b at the center of the test piece measured before and after the drop is 10 or less.
3. A molded article comprising the polypropylene resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Pull-open cap with hinge
JP1990045362A
Polypropylene resin composition
JP1998316727A
Propylene resin molded item
JP2001348469A
Drink bottle cap
JP2009084393A
Propylene-based resin composition for medical member, and medical member
JP2014212916A